High Resolution Quantitative Trait Locus Mapping and Whole Genome Sequencing Enable the Design of an Anthocyanidin Reductase-Specific Homoeo-Allelic Marker for Fruit Colour Improvement in Octoploid Strawberry (Fragaria × ananassa) - Labadie, Marc; Vallin, Guillaume; Potier, Aline; Petit, Aurélie; Ring, Ludwig; Hoffmann, Thomas; Gaston, Amèlia; Munoz-Blanco, Juan; Caballero, José L.; Schwab, Wilfried; Rothan, Christophe; Denoyes, Béatrice (Frontiers in Plant Science, 2022)
Fruit colour is central to the sensorial and nutritional quality of strawberry fruit and is therefore a major target in breeding programs of the octoploid cultivated strawberry (Fragaria x ananassa). The red colour of the fruit is caused by the accumulation of anthocyanins, which are water-soluble flavonoids. To facilitate molecular breeding, here we have mapped with high resolution fruit colour QTLs (COLOUR, scored visually as in selection programs) and associated flavonoid mQTLs (5 anthocyanins compounds together with 8 flavonols and flavan-3-ols) to specific subgenomes of cultivated strawberry. Two main colour-related QTLs were located on the LG3A linkage group (F. vesca subgenome). Genetic mapping, transcriptome analysis and whole genome sequencing enabled the detection of a homoeo-allelic variant of ANTHOCYANIDIN REDUCTASE (ANR) underlying the major male M3A COLOUR and pelargonidin-3-glucoside (PgGs) QTLs (up to ~20% of explained variance). Consistent with previously published functional studies, ANR transcript abundance was inversely related with PgGs content in contrasted progeny individuals. Genetic segregation analyses further indicated that a molecular marker designed after an 18 bp deletion found in the 5’UTR of the candidate ANR homoeo-allelic variant is effective in identifying genotypes with intense red fruit colour. Our study provides insights into the genetic and molecular control of colour-related traits in strawberry and further defines a genetic marker for marker-assisted selection of new strawberry varieties with improved colour. Noteworthy, the QTLs detected and the underlying candidate genes are different from those described to date, emphasizing the importance of screening a wide diversity of genetic resources in strawberry.